Unusual familial cystic kidney disease: combining fine radiologic and genetic evaluation to solve the case - Sylvain Bodard; Rim Nabbout; Olivier Hélénon; Bertrand Knebelmann (BMC Nephrology)
Abstract Background Autosomal dominant polycystic kidney disease (ADPKD) is the most prevalent hereditary kidney disease, characterized by enlarged kidneys with numerous cysts, high blood pressure, and a variety of extrarenal complications. This disease is a significant cause of renal failure and requires accurate differentiation from other cystic kidney diseases, especially when family history does not clearly indicate ADPKD. This is crucial due to differences in prognosis, treatment, and familial implications. Advanced molecular genetics and imaging techniques are employed to diagnose and assess the prognosis of patients and their families. Case presentation The case study revolves around three patients from the same family—two sisters and one daughter—referred to a nephrology department for ADPKD management. The initial proband, a 42-year-old woman, experienced abdominal discomfort leading to an ultrasound that suggested ADPKD. However, MRI findings indicated standard-sized kidneys with bilateral parapelvic cysts, and no genetic markers for ADPKD were found. Her sister, presenting with controlled hypertension and similar ultrasound findings, also had her initial ADPKD diagnosis refuted by MRI and genetic testing, which revealed no significant mutations. The daughter, however, exhibited a different scenario with enlarged kidneys and multiple cysts characteristic of early-stage ADPKD. Genetic testing confirmed a deleterious PKD1 mutation, suggesting a de novo mutation, as her father showed no signs of the disease. Conclusion This study highlights the complexity and necessity of thorough diagnostic processes in suspected ADPKD cases to prevent misdiagnosis. The initial symptoms and imaging might misleadingly suggest ADPKD, as seen in the cases of the two older patients. Still, further detailed imaging and genetic analyses revealed no ADPKD, preventing inappropriate treatment and stress. In contrast, the younger patient's distinctive clinical and genetic profile confirmed ADPKD, illustrating the variability within even closely related individuals. Such detailed assessments are crucial in guiding correct treatment decisions and providing accurate familial counseling, emphasizing the importance of considering a broader spectrum of renal cystic disorders before confirming a diagnosis of ADPKD.